Extra-curricular work as a precondition for improving the health of schoolchildren. - Zaharina Evgenija Anatol'evna (Kharkov National Pedagogical University, 2011)
The problem of training future teachers of physical culture to the extra-curricular recreational and educational activities are considered. The study used the results of a questionnaire survey 135 students of higher educational establishments of Ukraine. An analysis of publications of Russian and Ukrainian scientists on the various forms of extra-curricular and extracurricular activities are analyzed. Based on the analysis of literary sources and conducted survey clarified some features of the training of future teachers of physical culture. The relevance and appropriateness of the chosen research problem are proved.